Coronary perivascular adipose tissue inflammation – An autopsy-based histomorphological study from a tertiary care hospital in South India - Chaithra Jadhav; Marak, Fremingston; Bharathi Pradeep (Asian Journal of Medical Sciences, 2023)
Background: The connective tissue around the blood vessels in the body (except cerebral vessels) is called perivascular adipose tissue (PVAT). Whenever there is a vascular pathology, PVAT increases in volume and becomes dysfunctional. This change promotes dedifferentiation of adipocytes. PVAT inflammation (PVATi) starts secreting anti-vasodilation and pro-inflammatory substance, leading to infiltration of inflammatory immune cells, endothelial dysfunction which initiates atherosclerosis followed by stenosis. It is now recognized that PVATi plays an important role in many vascular pathologies. Aims and Objectives: The objectives of the study were (1) to estimate the prevalence of coronary PVATi in an autopsy case, (2) to determine the coronary atherosclerotic changes and cardiac changes associated with PVATi, and (3) to correlate the association of PVATi with age and sex. Materials and Methods: Autopsy-based retrospective study done for a period of 1 year. From the autopsy requisition form, details such as age, gender, cause of death (COD), and gross findings of the organs were noted. The left coronary artery, right coronary artery, left anterior descending artery, left circumflex artery, and myocardium slides were reviewed microscopically to note the presence of PVATi, type of inflammatory infiltrate, atherosclerotic changes, percentage of stenosis, and associated cardiac changes. Range, frequencies, percentage, mean, standard deviation, and P-value were calculated. P<0.05 was taken as statistically significant. Results: Fifty-two cases showed PVATi among 400 autopsy cases performed during the period of 1 year. Forty-two cases were from males and 10 cases were from female. The most common COD noted was sudden death following chest pain. Ten cases showed PVATi involving major branches of the coronary artery. Thirty-six cases showed hypertrophic changes in myocardium. Acute myocardial infarction (MI) and old healed MI were noted in 7 and 23 cases, respectively. Conclusion: PVATi of coronary arteries has significant association with atherosclerosis and sudden death cardiac death.